Efficiency of injected anchors in connecting T–shaped masonry walls: a modelling approach. (27th September 2021) - Maione, A.; Casapulla, C.; Di Ludovico, M.; Prota, A.; Ceroni, F.
Highlights: Out-of-plane response of T-shaped masonry walls strengthened with injected anchors. Expected failure mechanism and horizontal capacity of the strengthened system. Experimental validation of the modelling approach. Design parameters affecting the horizontal capacity of strengthened systems. Preliminary design indications. Abstract: The seismic vulnerability of masonry buildings to out-of-plane failure mechanisms is frequently related to poor connections between orthogonal walls. The effectiveness of these connections represents a necessary condition to transfer the horizontal action to the in-plane stressed walls, allowing a box behaviour of the whole structure. Steel injected anchors or tie rods have been widely used in the past to improve connections between orthogonal walls, but proper analytical approaches to evaluate their effectiveness are still a matter of ongoing research. On the other hand, many seismic codes nowadays require assessing the safety improvement achieved with the strengthening interventions and the compatibility with masonry of many techniques has become a matter of debate in the light of the damage frequently caused by the same interventions. In this framework, the present paper focuses on the possibility of using injected anchors made of innovative materials, as pultruded CFRP tubes, in conjunction with traditional grout. For this purpose, a macro-block model, previously validated for the analysis of unreinforced stone masonry structures, is further developed to account for the contribution of these innovative strengthening systems in the out-of-plane response of masonry walls with T-shaped connections. The model, also considering the contributions of frictional resistances at masonry bed joints, is based on the kinematic approach of limit analysis. Literature results concerning full-scale tests of a T-shaped wall are assumed as a reference to validate the proposed approach. Then, the validated model is used to investigate the influence of some design parameters on the performance of the reinforced system and a first attempt to address the design of strengthening interventions with injected anchors is presented.